1999
DOI: 10.1007/s002560050550
|View full text |Cite
|
Sign up to set email alerts
|

Solitary infantile myofibromatosis involving the clavicle

Abstract: A rare case of solitary infantile myofibromatosis of bone is reported in the right clavicle of a 15-year-old boy. A radiograph demonstrated an osteolytic lesion with a sharp margin and a sclerotic rim. CT revealed a circumscribed lesion with slight expansion of the cortex. On MRI the lesion appeared isointense to muscle on T1-weighted images, bright on T2-weighted images, and showed marked gadolinium enhancement. The patient was well, without evidence of recurrence or metastasis, 4 years and 5 months following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Furthermore most of the previously described cases with a solitary lesion affecting bone involved the craniofacial bones [2] , [3] , [4] , [5] , [6] , [7] , and only a few cases affected the appendicular skeleton. Several affected extra-craniofacial sites have been sporadically reported, for example: femur [8] , tibia [9] , [10] , [11] , humerus [1] , ulna [12] , [1] , and clavicle [13] . The age of the patients was usually less than 2 years [3] , and no adult case has been reported, to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore most of the previously described cases with a solitary lesion affecting bone involved the craniofacial bones [2] , [3] , [4] , [5] , [6] , [7] , and only a few cases affected the appendicular skeleton. Several affected extra-craniofacial sites have been sporadically reported, for example: femur [8] , tibia [9] , [10] , [11] , humerus [1] , ulna [12] , [1] , and clavicle [13] . The age of the patients was usually less than 2 years [3] , and no adult case has been reported, to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few reports of myofibromas in adults [2] , [3] , [7] , [9] , [11] , [12] , [13] , [14] , [15] . Daimaru et al reported five cases of myofibromas in adult patients [13] . The tumors clinically presented as superficial, painless, and slowly enlarging nodules, usually of more than 10 years׳ duration, that occurred in the upper (two cases) and lower (two cases) extremities or the buccal mucosa (one case).…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 , 15 , 22 ] Expansile mass may also be accompanied by pathological fracture. [ 10 , 14 , 15 , 18 , 19 ] MRI usually shows a hypo- to isointense signal with adjacent muscle on T1-weighted images and a homogeneous or inhomogeneous hyperintense signal on T2-weighted images with marked enhancement on postcontrast T1-weighted images. [ 10 , 22 , 23 ] Sometimes, the mass has nonenhanced central portion, called a “target sign”, which corresponds to the presence of central necrosis on pathological examination.…”
Section: Discussionmentioning
confidence: 99%
“…Our results differ from the typical MRI appearance of myofibromatosis. Most commonly, a low to moderately low intensity signal on T1, high intensity signal on T2 13,26,27 and marked enhancement post contrast are encountered 26,27 .…”
Section: Discussionmentioning
confidence: 99%